The Accessibility of Parkinson's Disease Medication in Kenya: Results of a National Survey. Issue 4 (9th January 2016) - Mokaya, Jolynne; Dotchin, Catherine L.; Gray, William K.; Hooker, Juzar; Walker, Richard W.
Abstract: Background: There is a dearth of knowledge about the availability and affordability of the different drug treatments for Parkinson's disease (PD) across sub‐Saharan Africa (SSA). We aimed to determine the availability and affordability of drugs for treating PD in Kenya. Methods: A facility‐based survey was conducted in selected medicine outlets (pharmacies) in what were formerly the headquarter towns of the eight provinces of Kenya. We used the World Health Organization/Health Action International methodology to obtain data for drugs used to treat PD. Unit price for each drug was obtained. Results: Forty‐eight outlets were visited in total, six in each of Kenya's eight provinces. Levodopa (L‐dopa) was available in only 24 (50.0%) outlets. Only one public pharmacy soldl ‐dopa (14 were private and nine were other types of outlet). Ergot‐derived dopamine agonists (DAs) and anticholinergics were available in 37 and 35 outlets, respectively. Monoamine‐oxidase inhibitors, non‐ergot‐derived DAs, and catechol‐ O ‐methyl transferase inhibitors were available in four, two and zero outlets, respectively. Mean cost of 100l ‐dopa tablets was 48.2, though costs varied widely (range, 28.2–82.4). Only five outlets consideredl ‐dopa affordable, all of which sold 100 tablets for less than 31. Conclusion: There is a lack of availability of PD drugs in Kenya, particularly in public pharmacies, where costs are generally lower. Few pharmacists consider the drugs available to be affordable. If PD is to be effectively managed in Kenya, then strategies are needed to increase the availability and affordability of medication.